Sacral Marjolin's Ulcer: A Case of Delayed Diagnosis in a Paraplegic Patient - Ahmad, Wafiuddin; Liang, Goh Kian; Yi, Kow Ren; Taufik, Taufik (IIUM Medical Journal Malaysia, 2020)
Marjolin's ulcer is a rare and aggressive malignancy ulcerating squamous cell carcinoma of the skin presenting in a previously injured or chronically inflamed area. However, the diagnosis may be delayed particularly in chronic sacral sores due the insidious onset and low index of suspicion, resulting in suboptimal management and poor outcome.A 42-year-old Malay gentleman sustained complete spinal cord injury in 1998 and consequently paraplegic. Five years prior to presentation in 2019, he noted a small ulceration at the sacral area. Despite regular dressing and multiple hospitalization for wound debridement, the wound condition worsened and involved gluteus and right thigh,associated with loss of weight and appetite. The patient also had rectocutaneous fistula and subsequently underwent diversion colostomy. Upon presentation at our hospital, he was in septic shock requiring prolonged inotropic support. Local examination revealed a 20x40cm sacral and gluteal sores with copious purulent discharge and presence of slough intermixed with granulation tissue and irregular looking mass. Diagnosis of septic shock secondary to infected Marjolin's ulcer was made. Four quadrant biopsies were taken, and the histopathological examination revealed well-differentiated squamous cell carcinoma. CT thorax, abdomen and pelvis revealed multiple calcified lung nodule, local spread of squamous cell carcinoma and invasion into whole rectum, posterior part of bladder , prostate gland ,and posterior part of penis . In view of the extensive local disease and lung metastases, patient opted for palliative treatment.The sepsis was unresolved and the wound remained infected, the patient succumbed and died due to the sepsis.A high index of suspicion and prompt oncologic management is required in managing chronic non- healing ulcer. An early referral to oncologic centre will improve the prognosis of patients with Marjolin's ulcer. Late diagnosis and superimposed infection will ultimately result in very poor outcome.